Abscisic acid-mediated induction of FLAVIN-CONTAINING MONOOXYGENASE 2 leads to reduced accumulation of methylthioalkyl glucosinolates in Arabidopsis thaliana. (February 2021) - Li, Yimeng; Li, Rui; Sawada, Yuji; Boerzhijin, Surina; Kuwahara, Ayuko; Sato, Muneo; Hirai, Masami Yokota
Highlights: Glucose treatment induced Arabidopsis FMOGS-OX2/4 expression independent of known MYB/MYC. FMOGS-OX2/4 induction is partially regulated by ABA through regulators ABI1 and ABI2. FMOGS-OX2 upregulation resulted in a decrease in methylthioalkyl glucosinolates. FMOGS-OX2 upregulation resulted in an increase in methylsulfinylalkyl glucosinolates. Abstract: Side-chain modification contributes to the structural diversity of aliphatic glucosinolates (GSLs), a class of sulfur-containing secondary metabolites found in Brassicales. The first step in side-chain modification of aliphatic GSLs is the S -oxygenation of the methylthioalkyl (MT) moiety to the methylsulfinylalkyl (MS) moiety. This reaction is catalyzed by flavin-containing monooxygenase (FMOGS-OX ), which is encoded by seven genes in Arabidopsis thaliana . Therefore, the regulation of FMOGS-OX gene expression is key to controlling side-chain structural diversity. In this study, we demonstrated that the expression of FMOGS-OX2 and FMOGS-OX4 was induced by glucose treatment, independent of MYB28/29 and MYC2/3/4, the transcription factors that positively regulate aliphatic GSL biosynthesis. Glucose treatment of the abscisic acid (ABA)-related mutants indicated that glucose-triggered upregulation of FMOGS-OX2 and FMOGS-OX4 was partially regulated by ABA through the key negative regulators ABI1 and ABI2, and the positive regulator SnRK2, but not via the transcription factor ABI5. In wild-type plants, glucose treatment drastically reduced the accumulation of 4-methylthiobutyl (4MT) GSL, whereas a decrease in 4MT GSL was not observed in the fmogs-ox2, abi1-1, abi2-1, aba2-1, or aba3-1 mutants. This result indicated that the decreased accumulation of 4MT GSL by glucose treatment was attributed to upregulation of FMOGS-OX2 via the ABA signaling pathway.